2001
DOI: 10.1007/s001090100270
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the human prion protein promoter in neuronal and endothelial cells

Abstract: Human prion diseases such as Creutzfeld-Jakob disease and kuru are of major medical and biological importance because of their fatal course, epidemic potential, and unique pathophysiology. Endogenous expression of the normal cellular prion protein (PrP(C)) is necessary for infection and prion replication. However, knowledge of human PrP(C) gene regulation is rudimentary. We therefore cloned1543 bp of the 5' untranslated and promoter region of the PrP gene. Using transient transfection assays, the full-length p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Measurements of PrP c Promoter Transactivation-The 1543-bp 5Ј promoter region of the human PrP c gene or serial 5Ј-truncated constructs (1303-, 909-, 567-, 284-, and 131-bp constructs) were subcloned into the luciferase reporter vector pGL3 basic and used to measure PrP c promoter transactivation, as extensively described (25). Cells grown in 12-well plates were co-transfected with full-length or mutant PrP c promoterluciferase, ␤-galactosidase (to normalize transfection efficiencies), and the indicated cDNAs with Lipofectamine (HEK293 cells) or with the Amaxa Nucleofector TM kit (mouse embryonic fibroblasts).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of PrP c Promoter Transactivation-The 1543-bp 5Ј promoter region of the human PrP c gene or serial 5Ј-truncated constructs (1303-, 909-, 567-, 284-, and 131-bp constructs) were subcloned into the luciferase reporter vector pGL3 basic and used to measure PrP c promoter transactivation, as extensively described (25). Cells grown in 12-well plates were co-transfected with full-length or mutant PrP c promoterluciferase, ␤-galactosidase (to normalize transfection efficiencies), and the indicated cDNAs with Lipofectamine (HEK293 cells) or with the Amaxa Nucleofector TM kit (mouse embryonic fibroblasts).…”
Section: Methodsmentioning
confidence: 99%
“…10A). We first examined whether these two putative ERK1/2-regulated sites indeed behaved as PrP c transcription activators by means of deletion analysis of the 5Ј PrP c promoter region (25). Deletion of the Sp1 binding site does not affect luciferase activity (compare Ϫ1543 and Ϫ1303 constructs; Fig.…”
Section: Erk Controls Prpmentioning
confidence: 99%
“…However, little is known about the molecular pathways underlying these regulatory events. The functional characterization of the human prion promoter (Funke-Kaiser et al, 2001) identified two regulatory regions where sequence analysis revealed consensus sequences for AP-1, Sp1, and Sp2 factors (Mahal et al, 2001;Bellingham et al, 2009). Our in silico analysis of the human PRioN protein (PRNP) gene promoter also revealed a motif partly matching the binding sequence targeted by the oncogene p53.…”
Section: Introductionmentioning
confidence: 78%
“…Molecular cloning of the human PRNP gene promoter facilitated the understanding of the transcriptional regulation of PrP c (Funke-Kaiser et al, 2001;Mahal et al, 2001). Thus, the 5Ј-flanking region of PRNP revealed several putative binding sites for transcription factors including Sp1, AP1, AP2, c-REL, and Nkx2-5, suggesting stimulus-dependent and cellspecific mechanisms of transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have previously identified TFBSs that are potentially associated with PRNP gene regulation in sheep, cattle, humans and rats (Saeki et al, 1996;Inoue et al, 1997;Baybutt & Manson, 1997;Hills et al, 2001;Funke-Kaiser et al, 2001;McCormack et al, 2002;Sander et al, 2004Sander et al, , 2005Premzl et al, 2005). Using Biobase MATCH software to search the TRANSFAC database (Matys et al, 2003), nine TFBSs were identified that were gained or lost in the promoter haplotypes (Supplementary Table S5).…”
Section: Scrapie-negativementioning
confidence: 99%